A review on electrical characterization techniques performed to study the device performance of quantum dot sensitized solar cells. (1st January 2018) - Kusuma, J.; Geetha Balakrishna, R.
Graphical abstract: Abstract: Third generation quantum dot sensitized solar cells (QDSSC) presents as one of the most promising, cost-effective and an alternative to traditional silicon cells due to its distinguished features. The overall cell efficiency still remains as low as 13% for QDSSC. The factors responsible for the low efficiency needs mere knowledge on the physics of devices and materials and its influence on its performance. In this view, the present paper discusses on the different electrical measurement techniques like current–voltage studies, photon conversion efficiency, impedance studies, capacitance measurements, lifetime measurements, imaging and Hall Effect techniques that helps in identifying the underlying problems and optimizing the processes and parameters towards better performance of the device. Also, the article opens up the scope to extend some techniques to QDSSC, which otherwise are being presently used only for existing reality of solar cells. These measurement techniques highlights as efficient performance indicators in yielding results for consistent device performance and also in improvising the device performance with greater reproducibility.